An Analysis of the Islamic and Conventional Banking Profitability in Palestine - Abusharbeh, Mohmad Tawfiq (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
Abstract: An Analysis of the Islamic and Conventional Banking Profitability in Palestine. The research paper examines the performance of profitability of Islamic banks against conventional banks for the period of 2005 to 2010. Two alternative measurements of banking profitability such as Return on Equity (ROE) and Return on Assets (ROA) are used to examine whether there is any differences of profit rate between Islamic, local and foreign conventional banks. The study concludes that Islamic banks generally provide the similar profit rate compared to local banks, however Islamic banks provide lower profit rate compared to foreign banks. Finally the findings also suggest that there is no statistical significant difference in mean return between the Islamic banks, local and foreign banks in Palestine. The study recommends the critical needs for Islamic regulation in order to improve the role of Islamic banking industry in Palestine. Abstrak: Analisis Profitabilitas Bank Islam dan Bank Konvensional di Palestina. Riset ini mengkaji kinerja profi tabilitas bank Islam dibandingkan dengan bank konvensional selama periode 2005-2010. Dua alternatif pengukuran untuk menilai kinerja profi tabilitas bank yaitu Return on Equity (ROE) dan Return on Assets (ROA) digunakan untuk melihat apakah ada perbedaan tingkat laba antara bank Islam, lokal dan bank konvensional asing. Studi ini menyimpulkan bahwa bank Islam memberikan laba yang setingkat dengan bank lokal, namun tingkat laba yang lebih rendah dibandingkan bank asing. Akhirnya, studi ini juga mengindikasikan bahwa tidak ada perbedaan statistik yang sigifi kan pada tingkat pengembalian rata-rata antara bank Islam, lokal dan asing. Studi ini merekomedasikan kebutuhan akan regulasi Islami untuk memberikan kontribusi yang lebih baik di Palestina.